2017
DOI: 10.1038/ijir.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress evoked damages on rat sperm and attenuated antioxidant status on consumption of aspartame

Abstract: Although several studies on toxic effect of aspartame metabolite have been studied, controversial reports over the use of aspartame owing to the fact that it releases methanol as one of its metabolite during metabolism exist. This present study is proposed to investigate whether aspartame (40 mg kg b.wt) administration for 90 days could induce oxidative stress and alter antioxidant status of epididymal sperm in Wistar strain male albino rats. To mimic the human methanol metabolism, methotrexate (MTX)-treated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…The MDA and pC are an important indicator of oxidative damage to macromolecules such as lipid and protein, respectively (Alghasham et al 2013 MSG increased the level of MDA and pC in epididymis and prostate gland. Administration of aspartame, an artificial sweetener used in the food was found to cause increased in MDA level of sperm due to the increased formation of ROS (Ashok et al 2017). furthermore, the excessive intake of MSG leads to the increased of glutamate level in circulation.…”
Section: Resultsmentioning
confidence: 99%
“…The MDA and pC are an important indicator of oxidative damage to macromolecules such as lipid and protein, respectively (Alghasham et al 2013 MSG increased the level of MDA and pC in epididymis and prostate gland. Administration of aspartame, an artificial sweetener used in the food was found to cause increased in MDA level of sperm due to the increased formation of ROS (Ashok et al 2017). furthermore, the excessive intake of MSG leads to the increased of glutamate level in circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Aspartame is 200 times sweeter than sucrose [Magnuson et al, 2007] and consists of phenylalanine, aspartic acid, and methanol [Humphries et al, 2008]. While there are studies that report beneficial roles of aspartame [Tordoff and Alleva, 1990;Blackburn et al, 1997;Raben et al, 2002;De la Hunty et al, 2006], others suggest it as a cause of different ailments, like headache [Lipton et al, 1989], vestibulocochlear toxicity [Pisarik and Kai, 2009], oxidative stress [Ashok et al, 2017], and even cancer [Soffritti et al, 2005;Pandurangan et al, 2016]. Some studies in recent years have reported that artificial sweeteners, including aspartame, change the composition of gut microbiota and induce glucose intolerance [Bokulich and Blaser, 2014;Palmnäs et al, 2014;Suez et al, 2014Suez et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Among these metabolites, methanol is oxidized to formaldehyde and then into formate, accompanied by the formation of superoxide anion and hydrogen peroxide. It has been suggested that both aspartate and methanol may have deleterious effects on the nervous system by inducing the oxidative stress . Sucralose is synthesized from sucrose by substituting three hydroxyl groups of sucrose with chlorine atoms.…”
Section: Introductionmentioning
confidence: 99%